Automatic Adjustment on the Ministry of Finance’s Expenditures 2022–2024 - Ladiesha Anggela Nuzulqurana; Hilman Abdul Halim (Eduvest - Journal of Universal Studies, 2025)
To survive and strengthen the financial sector during and after the pandemic, the Indonesian Government introduced a technocratic innovation policy called the automatic adjustment policy (blocking budget) from 2022 to 2024. This policy prioritizes activities and types of spending for ministries and institutions. The ministry of finance, the main fiscal manager, had a spending realization of 97.81% in 2022 and 97.47% in 2023. This is higher than the average budget absorption of 95% for ministries and institutions each year, there are concerns that the automatic adjustment at the ministry of finance may not run optimally. The research focuses on how the ministry of finance enforces automatic adjustment from 2022 to 2024. It used a qualitative thematic approach. Data were obtained through interviews with the budgeting department, documentation, document studies, and literature studies. The results show that the ministry of finance implemented automatic adjustment based on national policy criteria and priority needs. This policy strengthens the culture of efficiency, better spending, and the momentum for new work patterns in the ministry of finance, while also considering organizational and national goals.